Predictors of outcome for cats with ureteral obstructions after interventional management using ureteral stents or a subcutaneous ureteral bypass device. Issue 12 (December 2013) - Horowitz, Cara; Berent, Allyson; Weisse, Chick; Langston, Cathy; Bagley, Demetrius
Novel treatment alternatives for feline ureteral obstruction(s) include placement of a double pigtail ureteral stent and a subcutaneous ureteral bypass (SUB) device. This study evaluated parameters for the prediction of hospitalization times, peri-operative survival, renal recovery and long-term survival in cats with benign ureteral obstructions after successful decompression with either a ureteral stent or SUB device. The medical records of 41 cats treated for benign ureteral obstruction(s) were retrospectively reviewed. Preoperative historical, biochemical and imaging parameters, along with intra- and postoperative biochemical parameters and complications were evaluated for predictors of hospitalization length, survival to discharge, 3-, 6- and 9-month post-procedure creatinine, and overall survival time. All patients had successful decompression of their renal pelvis. Hospitalization time was positively associated with presenting creatinine, perioperative complications, post-procedure creatinine and potassium, but was negatively associated with post-procedure sodium. No parameters were associated with survival to discharge. A higher creatinine at discharge was positively associated with a higher creatinine at follow-up. A decreased overall survival was associated with a higher presenting blood urea nitrogen, higher creatinine at hospital discharge and in overhydrated patients during hospitalization. Cats with International Renal Interest Society stage 1 and 2 kidney disease, versus stage 3 and 4, at 3 months and 6 months post-procedure, lived longer. Cats with ureteral obstruction(s) treated with a ureteral stent or SUB device had an overall good survival and no admitting parameter was associated with survival to discharge. No single parameter was associated with all outcomes in this study, making predicting patient survival and cost prior to ureteral decompression difficult.